ANALISIS EKSERGI KIMIA SISTEM KONVERSI LIMBAH PADAT CANGKANG SAWIT DENGAN TEKNIK PIROLISIS PLASMA - Purawiardi , Ibrahim; Aribah, Putri; Aminuddin, Aminuddin; Dimyati , Arbi; Sari, Yessie Widya; Elbersen, Wolter; Maddu, Akhiruddin (Jurnal Rekayasa Mesin, 2025)
Chemical exergy analysis was commonly used to evaluate the effectiveness of some energy conversions derived from biomass. In this study, this analysis was conducted to evaluate oil palm kernel shell conversion via high-temperature plasma treatment. The plasma treatment was conducted with a DC power source with a voltage of 12 V and current variations of 40, 50, 60, 70, and 80 A. This chemical exergy efficiency was calculated based on gas chromatography (GC) analytical results. The calculated results showed that the chemical exergy efficiency increased exponentially as the current increased. Thus, based on this result, the arc plasma treatment is more recommended to be applied for the pyrolysis application of oil palm kernel shell than its gasification.